2020
DOI: 10.1177/0954406220916493
|View full text |Cite
|
Sign up to set email alerts
|

Transient performance of the mixed flow and radial flow variable geometry turbines for an automotive turbocharger

Abstract: In our previous paper, the steady-state test results of a mixed flow turbine with variable nozzle vanes for a turbocharger are reported. In this paper, the transient response of the same mixed flow turbine along with that of a similarly sized radial flow turbine is presented. The turbine size is suitable for handling the flow capacity of the diesel engines with swept volume up to 1.5 L. The previous experimental test set up is modified by adding a quick-release valve – actuation system before the turbine inlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This cost-effective solution typically uses an external actuator augmented on an otherwise traditional turbocharger to pivot the angle of vanes surrounding the turbine blades (pivot vane) that capture energy from the flow of exhaust gases or a moving-wall. 10 An aggressive vane angle allows the turbine to capture more energy at low speed and load conditions, where a conventional fixed geometry turbocharger typically suffers. At high speed and load conditions the vane angle can be made much less aggressive, which improves efficiency of the turbocharger.…”
Section: Introductionmentioning
confidence: 99%
“…This cost-effective solution typically uses an external actuator augmented on an otherwise traditional turbocharger to pivot the angle of vanes surrounding the turbine blades (pivot vane) that capture energy from the flow of exhaust gases or a moving-wall. 10 An aggressive vane angle allows the turbine to capture more energy at low speed and load conditions, where a conventional fixed geometry turbocharger typically suffers. At high speed and load conditions the vane angle can be made much less aggressive, which improves efficiency of the turbocharger.…”
Section: Introductionmentioning
confidence: 99%
“…While the indirect method takes the turbocharger as a subpart of the ICE, the transient performance of the turbocharger is evaluated by analyzing the crankshaft speed, power, torque, and other parameters of the ICE in the engine bench test. 14 It is called the direct method on the transient response of the turbocharged engines. The typical transient process is studied by numerical simulation or bench test, and transient performance is evaluated by engine power, fuel consumption, emissions, or other indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed an improvement by 3.66% and 2.18% of the cycle-averaged power and mass flow rate respectively. Later, Kannan et al 17 carried out an experimental study for comparing the transient response between radial and mixed flow turbines equipped with nozzle vanes. They showed that the transient response of the radial turbine makes a delay by about 0.09 s compared to the mixed flow turbine.…”
Section: Introductionmentioning
confidence: 99%